Quantitative assessment of the need for referrals from Family Health Units and Basic Health Units in the city of Cascavel-PR based on stratification by epidemiological district (Research, Society and Development, 2023)
In this study, we sought to evaluate the disproportion of the numbers of referrals in the years 2017 to 2020 of professionals from different epidemiological districts that work in Basic Health Units (BHU) compared to those that work in Family Health Units (FHU) in the municipality of Cascavel-PR. The digital/electronic reports provided by the electronic medical records system (IPM) of the municipality of Cascavel from the years 2017 to 2020 were used as the basis for the database. The analysis were performed in a cross-sectional qualitative and quantitative way of referrals during the years of the study, in greater emphasis the quantitative approach, through tabulated statistical analysis, bar graphs and pareto charts, using the Microsoft® Excel® 365.V16 tool, for the hypothesis test of the Poisson rate and confidence interval, Minitab® V.18.1 was used, the tests were applied with 95% confidence. Results: It was observed the existence of a high turnover of professionals within the municipality's PHC (primary health care), a fact that makes the data analysis difficult. Still, it was possible to observe that the FHUs have greater resolutivity when comparing the two health strategies. Conclusion: taking into account the data obtained in this research, it can be concluded that PHC have a higher resolution rate than BHU.